Análise comparativa in vitro da resistência friccional entre braquetes metálicos e estéticos - Rodrigues, Kelly Regina Thomé Portugal (2011)
The aim of this in vitro study was to compare the friction resistance among conventional and aesthetic orthodontic brackets with metal and vitreous slot with round and rectangular wires of different sections, simulating some situations without wire displacement, 2 mm of displacement and binding of 3o. A group of 125 brackets from 5 brands (Roth Standard, Composite, Elation, Invu and Radiance) was tested, 25 brackets for each brand. Five brackets were set on a device in order to simulate a top right hemi-arch (lateral and central incisors, canine, first and second premolars) and after that, the device was coupled on an universal testing machine EMIC DL2000. The archwires 0.016 , 0.018 and 0.017 x 0.025 NiTi were used on the no displacement and 2 mm displacement tests, while the wires 0.017 x 0.025 , 0.019 x 0.025 and 0.021 x 0.025 stainless steel were used to simulate the binding effect. Variance analysis and Tukey tests (p<0,05) were run to compare brackets with different archwires sizes and angulation. The study demonstrated that the polycarbonate aesthetic bracket Composite had the least friction in all archwires sizes tested. On the other hand, the monocrystalline ceramic bracket Radiance showed the greatest frictional resistance on the tests without wire displacement. Studies with archwire displacement and binding showed a statistically significant difference between the five accessories, of which Composite, Roth Standard, Elation, Invu and Radiance produced the highest friction resistance, in increasing order. Moreover, the insertion of a metal slot in the polycarbonate bracket Elation significantly reduced the friction. However, these friction was greater than the one from a metal bracket. To sum up, the insertion of a vitreous slot in the polycrystalline ceramic bracket Invu offered a greater surface smoothness, reducing consequently the friction and favoring the displacement.